Beware of Bipolar Transurethral Resection of Prostate in Patients with Previously Inserted Metallic Prostate Stapling Devices - Jianliang Liu; Nathan Lawrentschuk; Dixon T. S. Woon (Société Internationale d’Urologie Journal)
Metallic prostate stapling (e.g., UroLift) is a minimally invasive treatment option for men with bladder outlet obstruction from benign prostatic hyperplasia (BPH). While it provides rapid relief and preserves sexual function, unexpected interactions with other medical devices can compromise surgical procedures. In this letter, we highlight five cases where stapled metallic implants resulted in damage to bipolar energy device during transurethral resection of the prostate (TURP) and stimulation of obturator nerve. Laser may also reflect off metallic prostate implants which can result in laser equipment malfunction. Monopolar TURP should be considered in patients with existing metallic prostate implants who need further transurethral surgery for obstructive BPH to prevent bipolar instrument damage and obturator kick.